Toughening of epoxy by nanostructures with ABA triblock copolymers: An influence of organosilicon modification of block copolymer. Issue 2 (18th November 2021) - Li, Lei; Peng, Wenjun; Liu, Liyue; Zheng, Sixun
Abstract: In this work, we investigated the effect of organosilicon modification of an ABA triblock copolymer on the morphologies, thermal properties, and fracture toughness of epoxy thermosets. First, a poly(ε‐caprolactone)‐ block ‐poly(butadiene) ‐ block ‐poly(ε‐caprolactone) triblock copolymer was synthesized through the ring‐opening polymerization of ε‐caprolactone by using an α, ω‐dihydroxyl‐terminated polybutadiene as the macromolecular initiator. Thereafter, the triblock was organosilicon‐modified via the hydrosilylation of its midblock (viz. polybutadiene) with pentamethyldisiloxane. It was found that the organosilicon modification resulted in a switch of the nanostructure formation mechanism from reaction‐induced microphase separation to self‐assembly. As a consequence of the organosilicon modification, the morphological structures of the thermoset were significantly changed, and thus, the materials displayed different improvement in fracture toughness. In addition, the organosilicon modification further enhanced the surface hydrophobicity of the materials. Abstract : In this work, we investigated the effect of organosilicon modification of ABA triblock copolymer on the morphologies, thermal properties, and fracture toughness of epoxy thermosets.